A Morphometric Study of the Maxillary Artery and Lingula in Relation to Mandibular Ramus Osteotomies and TMJ Surgery - Balcioglu, Huseyin Avni; Kilic, Cenk; Varol, Altan; Ozan, Hasan; Kocabiyik, Necdet; Yildirim, Mehmet (European Journal of Dentistry, 2010)
Objectives: Mandibular osteotomies and resection of the temporomandibular joint (TMJ) ankylosis are the mostly performed surgical procedures in the infratemporal fossa, which is in close proximity with the main trunk of the maxillary artery (MA). It is imperative to avoid the trunk or branches of the maxillary artery, otherwise, massive intraoperative or postoperative hemorrhage may develop. The goal of the study was to investigate the position of the maxillary artery in the infratemporal fossa and the lingula of the mandible.Methods: Significant landmarks were selected on the mandibles of formalin fixed cadavers, and the distances were measured between the maxillary artery and the bony landmarks with a digital caliper.Results: The average distances between the MA and the articular eminence, the medial cortex of the mandibular ramus, the inferior border of the pterygoid fovea and the mandibular notch were 1.67±0.48 mm, 5.38±2.47 mm, 16.84±1.74 mm, 2.94±0.52 mm, respectively. Course pattern of the MA at the subcondylar level was also mapped. In order to determine the position of the lingula, the average distances between the tip of the lingula and the mandibular notch, the inferior border of the ramus, the anterior margin of the ramus and posterior margin of the ramus were measured and found as 15.4±2.1 mm, 49.5±4.3 mm, 18.1±2.7 mm, 16.6±2.5 mm, respectively. No significant differences were found between the right and left sides, for all parameters.Conclusions: The studied parameters will assist and navigate clinicians to determine the anatomic proximity to the maxillary artery, and, minimize the risk of damaging the vessel. (Eur J Dent 2010;4:166-169)
Keywords: Maxillary artery; Lingula; Mandible; Vertical ramus osteotomy; Sagittal split osteotomy